Analysis of Factors Affecting Public Visit (KF) and Neonatus (KN) During the Covid-19 Pandemic in Area Martubung Health Center in 2021 - Sartika Nasution; Sarma Lumban Raja; Rina Hanum (Institute of Computer Science (IOCS), 2022)
The Covid-19 pandemic presents considerable challenges for maternal and newborn health services, resulting in a decrease in postpartum and neonatal visits. Data on postpartum and neonatal visits at the Martbung Health Center has decreased since the Covid-19 outbreak. To analyze the factors that influence postpartum and neonatal visits during the Covid-19 pandemic. Methods: This type of research is a mix method research. The total population is 34 people and all of them are used as samples. There were 10 research informants. Qualitative data analysis was carried out by means of data reduction, data presentation, and drawing conclusions. Results: Qualitatively, mothers have poor knowledge because they do not get health information about postpartum visits, have low education (SD/SMP), have just had their first child. Anxiety postpartum mothers are afraid of contracting Covid-19 because the virus spreads very quickly, postpartum mothers and babies are vulnerable to infection because their bodies are recovering. Postpartum mothers do not agree with the health protocol rules because they find it difficult to breathe using a mask. Postpartum and neonatal visits during the Covid-19 pandemic were influenced by knowledge, anxiety, and health protocol rules. It is recommended that village midwives carry out continuous counseling and intensify home visits during the Covid-19 pandemic so that the target for postpartum and neonatal visits is achieved.